2020
DOI: 10.1002/jeq2.20007
|View full text |Cite
|
Sign up to set email alerts
|

Midwestern cropping system effects on drainage water quality and crop yields

Abstract: Grain producers are challenged to maximize crop production while utilizing nutrients efficiently and minimizing negative impacts on water quality. There is a particular concern about nutrient export to the Gulf of Mexico via loss from subsurface drainage systems. The objective of this study was to investigate the effects of crop rotation, tillage, crop residue removal, swine manure applications, and cereal rye (Secale cereale L.) cover crops on nitrate‐N (NO3‐N) and total reactive phosphorus (TRP) loss via sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…However, water quality data were not reported. There have been several other studies conducted where swine manure was applied to tile‐drained land where water quality data were reported (e.g., Dougherty et al., 2020; Nila Rekha et al., 2011), but these studies did not include relevant soils information. Both studies concluded that although swine manure application increases nitrate concentrations in drainage water, best management practices can reduce nitrate loss to groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…However, water quality data were not reported. There have been several other studies conducted where swine manure was applied to tile‐drained land where water quality data were reported (e.g., Dougherty et al., 2020; Nila Rekha et al., 2011), but these studies did not include relevant soils information. Both studies concluded that although swine manure application increases nitrate concentrations in drainage water, best management practices can reduce nitrate loss to groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Doughtery et al. (2020) noted similar results in corn, but no effect on soybean yield unless a cover crop was introduced, at which point a significant reduction in yield occurred. Anapalli et al.…”
Section: Introductionmentioning
confidence: 87%
“…Although spring 2013 percolation was not the largest among the experimental years, it followed a dry year (2012) with a greater application rate where minimal leaching losses were observed. Poor crop growth and crop N uptake during dry years could leave substantial residual N in the soil, which could be flushed from the vadose zone in the following spring (Dougherty et al., 2020). As winter and spring precipitation for the Assiniboine‐Red River basin increase due to climate change, it is possible to expect increased NO 3 –N leaching losses in the future, mostly associated with high spring percolation.…”
Section: Discussionmentioning
confidence: 99%